Avaliação de um meio filtrante utilizando a Moringa oleifera Lam para tratamento de água produzida - Santos, Kryslaine Machado de Almeida dos (2015)
The disposal of liquid effluents of the oil industry, especially the produced water - wastewater that ranks first in quantity in this industrial branch, is very harmful to the environment, especially when it is not done the proper treatment or when the quality is out of Release limits set by environmental legislation. Thus, the treatment of these effluents has been the subject of many studies in the world, especially with regard to the opportunity to use alternative, viable and innovative ways to minimize such problems. This study aims to evaluate the filter media based on derivatives of Moringa oleifera Lam, to remove oils and greases produced water. The experiments were performed in the Alternative Technologies Laboratory (ATL), Department of Chemical Engineering (DEQ) of the Federal University of Sergipe (UFS), using synthetic produced water (APS) filtration tests performed in a pilot plant, using the following media filter: the complete pod, bark and moringa pie in average diameters respectively equal to 1.70 mm (G1); 0.84 mm (G2) and 1.18 mm (G3). For comparison, one test was made with the walnut shell filter media. Among these materials, which showed higher produced water oil removal (61.2%) was the moringa peel. We also calculated the filtrate flow for each bed and which had the highest flow was the MF2-G1 with 2.92 cm³ / cm².s. The use of the constituents of Moringa oleifera Lam, mainly bark, satisfactory results showed that motivate the development of future studies to make the material an alternative filter medium for treating water produced.